2021
DOI: 10.1051/0004-6361/201937432
|View full text |Cite
|
Sign up to set email alerts
|

Overdensity of VVV galaxies behind the Galactic bulge

Abstract: Context. The extragalactic vision we have through the Milky Way is very unclear. There is significant extinction of the optical emission from objects located in the region called the zone of avoidance (ZOA). NIR wavelengths are less affected by extinction, and therefore the infrared surveys in this zone are a potential source of astronomical discoveries. Nevertheless, these observations need to be compared with cosmological simulations in order to carry out high−accuracy studies. Aims. Our aim is to identify e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…In order to obtain the galaxy candidates, we used the star − galaxy separation parameters considering r 1/2 > 0.7 arcsec, CS < 0.5, and magnitude cut 10<Ks<16.5 mag, following the criteria from Galdeano et al (2021). The lower limit was selected in order to prevent saturated objects, and the upper limit represents a good approach to the reliability limit for visual inspection (Galdeano et al 2021). Under these constrains, we identified 4168 extended sources.…”
Section: Galaxy Detection and Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to obtain the galaxy candidates, we used the star − galaxy separation parameters considering r 1/2 > 0.7 arcsec, CS < 0.5, and magnitude cut 10<Ks<16.5 mag, following the criteria from Galdeano et al (2021). The lower limit was selected in order to prevent saturated objects, and the upper limit represents a good approach to the reliability limit for visual inspection (Galdeano et al 2021). Under these constrains, we identified 4168 extended sources.…”
Section: Galaxy Detection and Classificationmentioning
confidence: 99%
“…In addition, Baravalle et al (2019) confirmed the existence of the first galaxy cluster, discovered by the VVV survey beyond the galactic disk, by using spectroscopic data from Flamingos-2 at GEM-INI Observatory. Recently, Galdeano et al (2021) found an unusual concentration of galaxies, in the VVV tile b204, detecting 624 extended sources, 607 of which are new galaxy candidates that have been cataloged for the first time. By exploring the spatial galaxy distribution in a small region of 15 arcmin, these authors found a noticeable overdensity, reinforcing this result with mock catalog information.…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain the galaxy candidates, we used the stargalaxy separation parameters considering r 1/2 > 0.7 arcsec, CS < 0.5, and magnitude cut 10 < K s < 16.5 mag, following the criteria from Galdeano et al (2021). The lower limit was selected in order to prevent saturated objects, and the upper limit represents a good approach to the reliability limit for visual inspection (Galdeano et al 2021). Under these constrains, we identified 4168 extended sources.…”
Section: Galaxy Detection and Classificationmentioning
confidence: 99%
“…In addition, Baravalle et al (2019) confirmed the existence of the first galaxy cluster, discovered by the VVV survey beyond the galactic disk, by using spectroscopic data from Flamingos-2 at GEMINI Observatory. Recently, Galdeano et al (2021) found an unusual concentration of galaxies, in the VVV tile b204, detecting 624 extended sources, 607 of which are new galaxy candidates that have been cataloged for the first time. By exploring the spatial galaxy distribution in a small region of 15 arcmin, these authors found a noticeable overdensity, reinforcing this result with mock catalog information.…”
Section: Introductionmentioning
confidence: 99%
“…Coldwell et al (2014) studied the NIR properties of the galaxy cluster Suzaku J1759-3450 (Mori et al 2013), located behind the Galactic bulge and discovered by the Suzaku (Mitsuda et al 2007) and Chandra (Weisskopf et al 2000) X-ray space telescopes. Recently, Galdeano et al (2021) used the VVV data and mock catalogues to analyse the b204 tile that corresponds to the Galactic bulge, reporting 607 new galaxy candidates, of which only 17 had previous identifications. Our main goal is to identify and characterize extragalactic sources on the regions behind the Southern disc of the MW.…”
Section: Introductionmentioning
confidence: 99%